Analysis and implementation of small business information system - Faltis, Jan; Pour, Jan; Poludvorná, Lucie; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2010)
This B.A. thesis deals with the preliminary analysis of a request as well as design and implementation of the first version of a solution for a small business information system. The introductory part focuses on achieving the required functionality which, in turn, forms the basis for a proposal. What follows is the selection of implementation conditions and the description of the implemented version of the system. In conclusion, the whole workflow is evaluated from the points of view of the company, the creator and the functionality achieved.
Vedoucí práce: Jan Pour
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2010
Rok obhajoby 2010
Keywords: informatika [obor bakal. práce]; bakalářské práce; bachelor's theses